Best Practices to Promote Learning at the Foundational Stage: A Study of an Anganwadi Centre in Assam - Koch, Priyanka; Sharma, Hitesh (THE PRIMARY TEACHER, 2025)
An integral part of the community, Anganwadi centres play a very important role in the holistic development of children in the foundational years by providing adequate care and stimulation. At that particular point of time in life when children are curious about everything happening around, it is important that the senses of a child are stimulated through observation, engaging them in multiple activities, storytelling and drama to help them experience learning in a joyful manner. In the foundational stage, care and concern is integral to bring the best in children. The importance of cognitive, social and emotional development is immense. Brain development in the early years of the child is very rapid. Foundational learning takes into account the learning of the child in settings like Anganwadis and Balwadis, ranging from the age group of 3–6 years, and in institutional settings ranging from the age group of 3–8 years. The study follows the functioning of an Anganwadi Centre in Lakhimpur district of Assam, throwing light upon the different pedagogical processes used by the Anganwadi workers for effective learning in the foundational years, with a special focus on the use of storytelling as an effective pedagogical approach.